Factors influencing the time-intensity curve analysis of contrast-enhanced ultrasound in kidney transplanted patients: Toward a standardized contrast-enhanced ultrasound examination - Friedl, Sarah; Jung, Ernst Michael; Bergler, Tobias; Tews, Hauke C.; Banas, Miriam C.; Banas, Bernhard; Putz, Franz Josef (Frontiers in Medicine, 2022)
Background: TIC-analysis (time-intensity-curve-analysis) based on CEUS (= contrast-enhanced ultrasound) provides quantifiable information about the microcirculation of different tissues. TIC-analysis of kidney transplantations is still a field of research and standardized study protocols are missing though being mandatory for the interpretation of TIC-parameters in the clinical context. The aim of this study was to evaluate the impact of different sizes and forms of ROIs (= region of interest) on the variance of different TIC-parameters and the level of interoperatorvariance between the different ROI methods in kidney transplantations. Methods: In 25 renal transplanted patients 33 CEUS of the transplanted kidney were performed and TIC-analysis with ROIs sized 5 mm2 (ROI5), 10 mm2 (ROI10) and ROIs circumscribing the outlines of anatomical regions (ROIAnat) were analysed based on CEUS examination. The TIC-analysis were repeated by a second independent operator for ROI5 and ROIAnat. Results: Statistical analysis revealed significant differences between TIC-parameters of different ROI methods and overall, the interoperatorvariance was low. But a greater ROI-surface (ROI10) led to higher values of the intensity parameters A and AUC compared to ROI5 (p < 0.05). The difference in the ROI-form led to high variation of certain TIC-parameters between ROI5 and ROIAnat in the myelon (intraclass correlation coefficient (A, ICC = 0.578 (0.139-0.793); TTP, ICC = 0.679 (0.344-0.842) [p < 0.05]). A mean variation of 1 cm of depth of ROI5 in the cortex did not show significant differences in the TIC-parameters, though there was an impact of depth of ROIAnat on the values of TIC-parameters. The interoperatorvariance in the cortex was low and equally for ROI5 and ROIAnat, but increased in the myelon, especially for ROIAnat. Further, the analysis revealed a strong correlation between the parameter AUC and the time interval applied for the TIC-analysis in cortex and myelon (r = 0.710, 0.674, p < 0.000). Conclusion: Our findings suggest the application of multiple ROIs of 5 mm2 in cortex and medulla to perform TIC-analysis of kidney transplants. For clinical interpretation of AUC, a standardised time-interval for TIC-analysis should be developed. After the standardisation of the TIC-analysis, the predictive value could be investigated in further studies.